Stratégies De Maintien Des ONG Locales En Côte d’Ivoire : Cas Des ONG OEuvrant Dans Le Domaine De L’eau, L’hygiène Et L’assainissement Dans La Zone Duekoué-Guiglo - Coulibaly Brahima (European Scientific Journal, ESJ, 2017)
Local NGOs working in the field of health and specifically the preventive encounter many difficulties. To survive, they use various strategies. Our goal is to show the strategies used by these players to stay on the field. Through a qualitative study, we administered an interview guide for managers and field staff of these organizations. The data collected showed that the actors of local NGOs carry out protection strategies, prevention, promotion and transformation.